A Five-Year Review of Tag Rugby Hand Injuries. Issue 10 (October 2016) - Joyce, C.W.; Woods, J.F.C.; Murphy, S.; Bollard, S.; Kelly, J.L.; Carroll, S.M.; O'Shaughnessy, M.
Abstract: Tag rugby is one of the fastest growing sports in Ireland. It is a soft-contact team game that is loosely based on the rugby league format except players try to remove Velcro tags from their opponents' shorts rather than engage in a typical rugby tackle. The purpose of this study was to examine all tag rugby associated hand injuries over a five-year period in three large tertiary referral hospitals in Ireland. Using the patient corresponding system, 228 patients with hand injury related tag rugby injuries were observed from 2010 to 2015. There were 138 males and 90 females in the study and over 40% of patients required surgery. Most of the patients were young professionals with an average age of 30. Twenty-five patients worked in the financial services whilst there were 23 teachers. Fractures accounted for 124 of the 228 injuries and mallet injuries accounted for 53. Eighty percent of all injuries occurred during the tackle. The mean number of days missed from work was 9.1 ± 13.8 days. These injuries resulted in an average of seven hospital appointments per patient. Considering it is a soft-contact sport, it is surprising the number of hand injuries that we have observed. Although safety measures have been introduced to decrease the number of hand injuries in recent years, there is a need for further improvements. Better player education about seeking prompt medical attention once an injury occurs, coupled with longer shorts worn by players may improve measures for the sport.